Non local Thirring model with spin ipping interactions - Iucci, Carlos Aníbal (2001)
We extend a nonlocal and noncovariant version of the Thirring model in order to describe a many-body system with spin-flipping interactions. By introducing a model with two fermion species we are able to avoid the use of nonabelian bosonization which is needed in a previous approach. We obtain a bosonized expression for the partition function, describing the dynamics of the collective modes of this system. By using the self-consistent harmonic approximation we found a formula for the gap of the spin-charge excitations as functional of arbitrary electron-electron potentials. © 2001 Elsevier Science B.V.